Jök 2021
DOI: 10.33799/jokull2021.71.021
|View full text |Cite
|
Sign up to set email alerts
|

The explosive, basaltic Katla eruption in 1918, south Iceland, II: Isopach map, ice cap deposition of tephra and layer volume

Abstract: Due to poor preservation and lack of proximal tephra thickness data, no comprehensive isopach map has existed for the tephra layer from the major eruption of the Katla volcano in 1918. We present such a map obtained by combining existing data on the thickness of the 1918 tephra in soil profiles with newly acquired data from the 590 km2 Mýrdalsjökull ice cap which covers the Katla caldera and its outer slopes. A tephra thickness of 20–30 m on the ice surface proximal to the vents is inferred from photos taken … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 0 publications
0
4
0
Order By: Relevance
“…bimodal GSD distribution presented here (Gudmundsson et al, 2021). Vertical sub-sampling the K1918 tephra layer to measure the GSD of would have provided additional stratigraphic information about the bimodal grain distributions however, because of the shallow depths of fallout considered in this study the cause of any vertical variations in GSD could be the result of two quite different processes.…”
Section: Sear and Grain Size Distributionmentioning
confidence: 82%
See 3 more Smart Citations
“…bimodal GSD distribution presented here (Gudmundsson et al, 2021). Vertical sub-sampling the K1918 tephra layer to measure the GSD of would have provided additional stratigraphic information about the bimodal grain distributions however, because of the shallow depths of fallout considered in this study the cause of any vertical variations in GSD could be the result of two quite different processes.…”
Section: Sear and Grain Size Distributionmentioning
confidence: 82%
“…A third of them had a reduced thickness, the rest maintained the same thickness or, in one instance, became thicker. The K1918 tephra is likely to have compacted by around 20 % since deposition (Gudmundsson et al, 2021;Larsen et al, 2021). Scaling-up to account for compaction indicated that retention of tephra was better than site measurements suggest, with all but one site losing less material than predicted and retaining a great portion of the initial deposit thickness.…”
Section: Sear and Tephra Deposit Retentionmentioning
confidence: 96%
See 2 more Smart Citations